A square‐shaped wrist as a predictor of carpal tunnel syndrome: A meta‐analysis. Issue 5 (24th July 2015) - Shiri, Rahman
ABSTRACT Introduction: This meta‐analysis aims to assess an association between wrist ratio (wrist thickness/wrist width) and carpal tunnel syndrome (CTS). Methods: Sixteen studies qualified for a random‐effects meta‐analysis. Results: Mean wrist ratio was higher in individuals with CTS compared with those without CTS [pooled mean difference 0.036, 95% confidence interval (CI) 0.025–0.046]. Pooled odds ratio (OR) of CTS for mean wrist ratio was 4.56 (95% CI 2.97–6.99), and for wrist ratio ≥0.70 vs. <0.70 it was 2.73 (95% CI 1.49–5.01). In addition, the pooled OR for a 1‐unit (0.01) increase in wrist ratio was 1.12 (CI 1.09–1.16). The association between wrist ratio and CTS did not differ between men and women. Moreover, there was no evidence of publication bias. Conclusions: This meta‐analysis suggests that a square‐shaped wrist is a predictor for CTS in both men and women. Future studies should explore whether a square‐shaped wrist can potentiate the adverse effects of obesity and occupational workloads on CTS. Muscle Nerve52: 709–713, 2015